DESIGNING THE DEVELOPMENT OF RELIGIOSITY IN EARLY CHILDHOOD ISLAMIC EDUCATION THROUGH THE ADDIE MODEL - Ratnasih, Teti; Suhartini, Andewi; Kurnia, Nia; Wardatul Hayati; Sham, Alwaris (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
The development of religiosity in early childhood requires a systematic learning plan so that the values of faith, worship, and morals can be optimally instilled during the golden age. This study aims to develop a design for enhancing religiosity in Early Childhood Islamic Education (PIAUD) through the application of the ADDIE model at RA Al Ihsan. The study uses a qualitative approach with a Research and Development (R&D) method, employing interviews, observations, and documentation with the head of RA and teachers. The data were analyzed using thematic analysis with triangulation to ensure data validity. The results indicate that integrating the ADDIE model with integrative, contextual, and participatory principles effectively internalizes religious values across all learning activities through habituation of worship, teacher role modeling, the use of creative media, and collaboration between the school and parents. The implementation of this design positively impacts the improvement of children’s religious behavior. This study concludes that the religiosity development model based on ADDIE is feasible to be used as a reference for other PIAUD institutions.